FOREST unbiased Galactic plane imaging survey with the Nobeyama 45 m telescope (FUGIN). VII. Molecular fraction of H i clouds. (23rd May 2020) - Nakanishi, Hiroyuki; Fujita, Shinji; Tachihara, Kengo; Izumi, Natsuko; Matsuo, Mitsuhiro; Umemoto, Tomofumi; Oasa, Yumiko; Inoue, Tsuyoshi
ABSTRACT: We analyze molecular-gas formation in neutral atomic hydrogen (H i ) clouds using the latest CO data, obtained from the FOREST (four-beam receiver system on the 45 m telescope) unbiased Galactic plane imaging survey with the Nobeyama 45 m telescope, and using H i data taken from the Very Large Array Galactic plane survey. We applied a dendrogram algorithm to the H i data cube to identify H i clouds, and we calculated the H i mass and molecular-gas mass by summing the CO line intensity within each H i cloud. On the basis of the results, we created a catalog of 5737 identified H i clouds with local standard of rest (LSR) velocity of V LSR ≤ −20 km s −1 in galactic longitude and latitude ranges of 20° ≤ l ≤ 50° and −1° ≤ b ≤ 1°, respectively. We found that most of the H i clouds are distributed within a Galactocentric distance of 16 kpc, and most of them are in the cold neutral medium phase. In addition, we determined that the high-mass end of the H i mass function is fitted well with a power-law function with an index of 2.3. Although two sequences of self-gravitating and diffuse clouds are expected to appear in the M  tot –$M_{\, {\rm H}_2}$ diagram according to previous works based on a plane-parallel model, the observational data show only a single sequence with large scattering within these two sequences. This implies that most of the clouds are mixtures of these two types of clouds. Moreover, we suggest the following scenario of molecular-gas formation: an H i -dominant cloud evolved with increasing H2 mass along a path of $M_{\, {\rm H}_2} \propto M_{\, \rm tot}^2$ by collecting diffuse gas before reaching and moving along the curves of the two sequences.